2007
DOI: 10.1289/ehp.9369
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disruptors and the Thyroid Gland—A Combined in Vitro and in Vivo Analysis of Potential New Biomarkers

Abstract: BackgroundThere is growing evidence that, in addition to the reproductive system, the hypothalamic–pituitary–thyroid axis is a target of endocrine-disrupting compounds (EDCs). However, this is not reflected adequately in current screening and assessment procedures for endocrine activity that to date determine only general parameters of thyroid function.Objective and MethodsWe used several in vitro and ex vivo assays in an attempt to identify suitable biomarkers for antithyroid action testing a selected panel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 74 publications
3
78
1
2
Order By: Relevance
“…expression is a useful biomarker of thyroid system function (Schmutzler et al, 2007). However, we did not observe the expected downregulation of tsh in the larvae from either the BDE-209 or nano-TiO 2 co-exposed groups.…”
Section: Discussioncontrasting
confidence: 79%
“…expression is a useful biomarker of thyroid system function (Schmutzler et al, 2007). However, we did not observe the expected downregulation of tsh in the larvae from either the BDE-209 or nano-TiO 2 co-exposed groups.…”
Section: Discussioncontrasting
confidence: 79%
“…TSH is encoded by the gene tshˇ. It has been demonstrated that tshˇ expression is a useful biomarker of the function of the thyroid system (Kratzsch and Pulzer, 2008;Schmutzler et al, 2007). In the present study, mRNA expression of tshˇ was significantly upregulated after TDCPP exposure.…”
Section: Discussionsupporting
confidence: 51%
“…Especially for TSH, the research by Choi et al (26) had suggested that RBP4 levels were associated with subclinical hypothyroidism. The retinol-binding protein is easily filtered through the kidney, forming a complex with transthyretin, a transport protein for T 4 , and this complex can prevent retinol-binding protein from being cleared by the kidney (33,34). It is possible that thyroid function could influence the excretion of RBP4 from the kidney.…”
Section: Figurementioning
confidence: 99%